The condition of the cardiovascular system in patients with relapsing-remitting multiple sclerosis - O. A. Traktirskaya; T. V. Adasheva; A. N. Boyko; E. V. Popova (Архивъ внутренней медицины)
The aim of the reserch was to study the state of the cardiovascular system, systemic inflammation and balance oxidant/|antioxidant in patients with relapsing-remitting multiple sclerosis.Material and methods. The study included 45 patients with relapsing-remitting multiple sclerosis (17 men and 28 women), age 28 [24; 32] years, disease duration 5.5 [2; 7] years. The control group included practically healthy patients, age 30 [25; 33] years. Patients with multiple sclerosis were examined neurologically with Expanded Disability Disease Score rating of disability. Instrumental methods included a comprehensive assessment of the cardiovascular system (24-hour Holter ECG monitoring and 24-hour blood pressure monitoring with determination of the daily arterial vascular stiffness, echocardiography). Laboratory methods included clinical and biochemical analysis of blood, lipid profile, glycemia, C-reactive protein. The indices of oxidative stress (acylhydroperoxide) and antioxidant protection (glutathione peroxidase, superoxide dismutase) were studied; a marker of endothelial dysfunction (vascular cellular adhesion molecule-1) were researched.Results. In the group of patients with multiple sclerosis, there was an increase in C-reactive protein, the marker of endothelial dysfunction compared with the control group (p<0.001). The indicators of oxidative stress and antioxidant protection were statistically significantly increased (p<0.001). According to the results of Daily Blood Pressure Monitoring the variability of systolic blood pressure and diastolic blood pressure during daytime hours was reduced comparison to the control group (р<0,026) and (p<0.002) respectively. The indicators of daily arterial stiffness in the group of patients with multiple sclerosis was statistically significantly increased (p<0.001). According to the results of Holter ECG monitoring, no heart rhythm disorder was detected in both groups. In the group of patients with remitting course of multiple sclerosis, an increase in the number of supraventricular extrasystoles was detected compared with the control group (p<0.005). The main indicators of echocardiography were within normal values, no significant differences between the groups were found.Conclusion. The study showed that multiple sclerosis patients are at risk of developing cardiovascular diseases and require increased attention to prevent the development.